1971
DOI: 10.1063/1.1659964
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field in Electrodeless Discharge

Abstract: A closed-form solution is given for the electromagnetic field in a cylindrical electrodeless discharge of infinite length in which the conductivity of the plasma is assumed to be complex and have a parabolic variation with plasma radius. The low-pressure ambipolar diffusion-controlled electrodeless discharge is closely approximated by this model. Solutions are presented for various values of the ratio of collision frequency to applied frequency and for various values of plasma conductivity. The variation in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…This was taken into consideration by Eckert [9]. Henrikson et al found a unified solution to the electrodynamic differential equations under the assumption of a parabolic distribution of the electric conductibility [10]. However, by considering such a profile, the variation of the ring discharge geometry becomes evident (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This was taken into consideration by Eckert [9]. Henrikson et al found a unified solution to the electrodynamic differential equations under the assumption of a parabolic distribution of the electric conductibility [10]. However, by considering such a profile, the variation of the ring discharge geometry becomes evident (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the growing interest in ICP, many works which devoted to the numerical study of the its characteristics have appeared. The nature of the distribution of the electromagnetic field in an inductive diffusive discharge was specified in the work of Henriksen et al [14]. There, the plasma conductivity was assumed to be complex and the radial distribution of the electron density was approximated by a quadratic parabolic function.…”
Section: Icp Simulationsmentioning
confidence: 99%
“…Eckert [265] used Bessel functions for the fields by including the average value of the electron density in Maxwell's equations, and a 'Schottky' radial profile [14] for the electron density to compute power deposition and impedance. Henriksen el al [273] found a closed-form solution for the electromagnetic fields assuming a parabolic density profile, and more recently Denneman [274] modelled lowpressure Ar-Hg discharges, again using a Schottky density profile and solving the coupled Maxwell equations numerically. For LPD operation, the skin depth 6 = (pawoo)-' [266,273], where U, is the average value of U , is generally large relative to the discharge dimensions, and E , follows closely the vacuum solution, so that the plasma influences the discharge through the magnetic field H,.…”
Section: Inductively Coupled Dischargesmentioning
confidence: 99%